Hydraulic Calculations of a Telescopic Water Intake - Lipin Andrey; Sepahvand Arash; Rustamova Narmin (Slovak Journal of Civil Engineering, 2023)
Telescopic water intake structures allow for the selective intake of water from the top layers of a reservoir. A telescopic water intake has a high degree of mobility, and a wide field of application; at the same time, it is very simple and convenient to operate. Despite these advantages, an exact calculation method for a telescopic water intake is lacking (Lipin, 2020; Lipin, 2022). Therefore, the purpose of this research is to develop an exact calculation method for a telescopic water intake. In order to perform this task, all the structural elements of a telescopic water intake were analyzed separately by means of existing hydraulic principles. The impact of the critical submergence depth of the water intake funnel on the operability of a telescopic water intake was studied, and an equation for the critical submergence depth calculation was proposed. The optimal range of the flow rate coefficient ( μ =0.30 - 0.45) was proposed for calculating the funnel flow rate, and the correlation between the flow rate and funnel inlet diameter was defined. The optimal curvature radius of the elbow was proposed. In order to verify the above mentioned parameters and correlations, analytical and numerical calculations of specific examples were performed. The results of the numerical modelling demonstrated that the critical submergence depth and shape of the water intake funnel, as defined by the analytical calculations, ensured its effective operation free of cavitation and vortexes. The analytically calculated dimensions of the telescopic column, following the numerical modelling results, provided normal hydraulic conditions without active cavitation. According to the numerical modelling, the proposed curvature radius of the elbow was sufficient to avoid significant cavitation and vortex formation in the elbow structure. This research can provide guidance for the design of telescopic water intake structures.